A bioreducible supramolecular nanoparticle gene delivery system based on cyclodextrin-conjugated polyaspartamide and adamantyl-terminated polyethylenimine. Issue 5 (19th January 2018) - Zhang, Yunti; Jiang, Qimin; Bi, Bo; Xu, Luming; Liu, Jia; Zhuo, Renxi; Jiang, Xulin
Abstract : Reduction degradable Pasp-SS-CD/Ad4 -PEI/pDNA supramolecular nanoparticles via host–guest interaction exhibited improved cellular internalization and higher gene transfection efficiency with lower cytotoxicity. Abstract : This article describes a novel reduction degradable supramolecular nanoparticle gene delivery system via host–guest interaction based on cyclodextrin-conjugated polyaspartamide with disulfide linkage (Pasp-SS-CD) and adamantyl-terminated polyethylenimine (Ad4 -PEI). The reduction responsiveness of Pasp-SS-CD and the Pasp-SS-CD/Ad4 -PEI/pDNA supramolecular nanoparticles (SNPs) in the presence ofdl -dithiothreitol (DTT) was confirmed by SEC-MALLS and DLS analysis, respectively. Compared with the Ad4 -PEI/pDNA polyplexes, the bioreducible supramolecular polycation/pDNA polyplexes exhibited smaller particle size, slightly higher zeta potential, lower cytotoxicity and hemolysis ratio, improved cellular internalization and higher gene transfection efficiency. It was found that introducing Pasp-SS-CD to assemble Ad4 -PEI could substantially enhance the tolerance of protein adsorption and maintain the gene transfer capacity of polycationic carriers, which might be beneficial for in vivo use. In addition, the cellular uptake pathway of the supramolecular polycation/pDNA polyplexes was investigated using different uptake inhibitors. The present study demonstrates that the proper assembly of cyclodextrin-conjugated polyaspartamide and adamantyl-terminated polyethylenimine is an effective strategy for the production of a new gene delivery system.